2012
DOI: 10.1186/1758-3284-4-6
|View full text |Cite|
|
Sign up to set email alerts
|

The effect of tobacco and alcohol and their reduction/cessation on mortality in oral cancer patients: short communication

Abstract: BackgroundThe use of tobacco is known to increase the incidence of developing oral cancer by 6 times, while the additive effect of drinking alcohol further increases the risk leading to higher rate of morbidity and mortality. In this short communication, we prospectively assessed the effect of tobacco smoking and alcohol drinking in oral cancer patients on the overall mortality from the disease, as well as the effect of smoking and drinking reduction/cessation at time of diagnosis on mortality in the same grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
42
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(45 citation statements)
references
References 26 publications
0
42
0
Order By: Relevance
“…Likewise, information on post-cancer diagnosis quit attempts, continuous abstinence, and/or tobacco cessation treatment use was omitted from all but a handful of papers (35, 39, 42, 44, 51-54, 56, 60, 73, 75, 80, 82, 83, 87, 90, 97, 103, 112, 129). Given limited data, we chose not to aggregate findings across studies.…”
Section: Resultsmentioning
confidence: 99%
“…Likewise, information on post-cancer diagnosis quit attempts, continuous abstinence, and/or tobacco cessation treatment use was omitted from all but a handful of papers (35, 39, 42, 44, 51-54, 56, 60, 73, 75, 80, 82, 83, 87, 90, 97, 103, 112, 129). Given limited data, we chose not to aggregate findings across studies.…”
Section: Resultsmentioning
confidence: 99%
“…15,16,24 However, other studies fail to show a significant difference in mortality based on smoking status after controlling for covariates. [25][26][27][28] In the head and neck cancer literature, smoking significantly increases overall mortality and cancer-specific mortality, 10,21,23,[29][30][31][32][33][34] and pack-years of smoking has a dose-response positive relationship with mortality, 23,30,35 yet some studies reported nonsignificant differences in overall mortality [36][37][38][39] and cancer-specific mortality 37,40 between smokers and nonsmokers. However, previous studies are limited by a one-time smoking assessment at or after diagnosis (mostly at diagnosis), their retrospective nature, inability to control for covariates, and short follow-up periods.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10] Tobacco cessation may improve outcomes in cancer patients, [11][12][13][14][15] and tobacco use assessment and cessation support are advocated by several national organizations including the American Society of Clinical Oncology (ASCO). 16 Recent guidelines have been developed by ASCO to help increase tobacco assessment and cessation, 17 but considerable work remains to provide tobacco cessation support for patients with cancer as part of standard clinical practice.…”
Section: Introductionmentioning
confidence: 99%